Evidence for phosphorylation and oligomeric assembly of presenilin 1 - Seeger, Mary (The National Academy of Sciences of the USA, 1997)
Pathogenic mutations in presenilin 1 (PS1) are associated with ≈50% of early-onset familial Alzheimer disease. PS1 is endoproteolytically cleaved to yield a 30-kDa N-terminal fragment (NTF) and an 18-kDa C-terminal fragment (CTF). Using COS7 cells transfected with human PS1, we have found that phorbol 12,13-dibutyrate and forskolin increase the state of phosphorylation of serine residues of the human CTF. Phosphorylation of the human CTF resulted in a shift in electrophoretic mobility from a single major species of 18 kDa to a doublet of 20–23 kDa. This mobility shift was also observed with human PS1 that had been transfected into mouse neuroblastoma (N2a) cells. Treatment of the phosphorylated CTF doublet with phage λ protein phosphatase eliminated the 20- to 23-kDa doublet while enhancing the 18-kDa species, consistent with the interpretation that the electrophoretic mobility shift was due to the addition of phosphate to the 18-kDa species. The NTF and CTF eluted from a gel filtration column at an estimated mass of over 100 kDa, suggesting that these fragments exist as an oligomerized species. Upon phosphorylation of the PS1 CTF, the apparent mass of the NTF- or CTF-containing oligomers was unchanged. Thus, the association of PS1 fragments may be maintained during cycles of phosphorylation/dephosphorylation of the PS1 CTF.